Internalizing Islamic Educational Philosophy Epistemology to Construct Generation Z Religiosity in the Post-Truth Era: A Qualitative Study at an Indonesian Islamic University - Husnul Khotimah; Noviana; Rahman Abadi; Noviriani; Mualimin; Mabruri (CV Putra Publisher, 2024)
The post-truth era, in which emotional resonance and identity-driven narratives often outweigh factual verification, has reshaped how Generation Z students access, interpret, and internalize religious knowledge through digital platforms. While prior studies have examined religious digital literacy and value-based character education in Indonesian Islamic schools, the role of the epistemology of Islamic educational philosophy in mediating Generation Z religiosity within non-state Islamic universities remains underexplored. This study investigates how the epistemological foundations of Islamic educational philosophy are internalized into the religiosity construction of Generation Z students at Universitas Islam Yasni Bungo, Jambi, Indonesia. Adopting a qualitative field-research design grounded in an interpretive paradigm, data were generated through semi-structured in-depth interviews with twelve students and six lecturers (purposively sampled), three months of participant observation across four academic and student-organization settings, and document analysis of curriculum syllabi, lecture materials, and student-organization records collected between February and April 2025. Data were analyzed using the Miles, Huberman, and Saldaña interactive model with both source and method triangulation to enhance trustworthiness, and member-checking with seven informants to verify interpretive accuracy. The analysis identified four interrelated mechanisms of epistemological internalization: dialogical and critical classroom practice rooted in the Qur'anic ḥiwār tradition; curricular integration that reconciles revelation, reason, and experience; lecturer modeling functioning as a hidden curriculum; and faith-based digital literacy emphasizing tabayyun. These mechanisms jointly cultivate a student religiosity that is reflective, rational, and resistant to disinformation rather than merely ritualistic. The study concludes that Islamic educational epistemology operates as a cognitive and normative filter that mediates students' engagement with digital religious discourse, offering a contextually grounded model for strengthening authentic religiosity in post-truth higher education.